MAKNA DAN JALANNYA UPACARA "PUPUTAN" DAN " SELAPANAN" DALAM ADAT UPACARA TRADISIONAL KELAHIRAN BAYI BAGI MASYARAKAT JAWA - Aswiyati, Indah (HOLISTIK, Journal Of Social and Culture, 2015)
Indonesia has the beauty of art and culture; e.g. the traditional custom ceremony 'Puputan' and 'Selapanan'. The ceremony is important to Javanese community related to the baby delivering process. This researched aimed to find the process of the traditional custom ceremony Puputan' and 'Selapanan' and the meaning of the symbols of the equipments used. Qualitative method was used to the object that the traditional custom ceremony baby delivering process in Javanese community to be investigated. 'Puputan' is the third phase in ceremony after the baby experienced the broken off the navel cord. 'Selapanan' is the last phase of ceremony in welcoming the baby after delivered for fifty-five days. There are many symbols appeared in the ceremony that reflect the philosophy and culture meanings. Keywords: Traditional custom ceremony baby deliverance